ANALISIS PENETAPAN UJRAH BARANG GADAI DITINJAU DARI FATWA DSN-MUI - moch zaenal azis muctharom (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
His research aims to explain the analysis of the determination of ujrah for pawned goods in terms of the DSN-MUI fatwa at Sharia Pawnshops. This research uses a qualitative research type with a descriptive method through interviews, observation, and documentation. The data collection was conducted using the interview method with the head of the Sharia Pawnshop and documentation from the Sharia Pawnshop, while for secondary data the researcher used documents, journals, regulations, books, and scientific works related to Rahn's theory. The National Sharia Council and the Indonesian Ulema Council on June 26, 2002, issued a fatwa Number: 25/DSN-MUI/III/2002. In the fatwa it is stated that: The amount of maintenance and storage costs for Marhun cannot be determined based on the loan amount. Meanwhile, in practice, the rental fees charged to customers will be different if the customer's loan amount is below the maximum loan value. While in practice the rental fee charged to customers will be different if the customer's loan amount is below the maximum loan value. The results of the study indicate that the calculation of ijarah fees applied by Perum Sharia Pawnshop is in accordance with DSN Fatwa Number: 25 / DSN-MUI / III / 2002, the calculation of ijarah is not based on the amount of the customer's loan but on the value of the collateral itself. Ijarah fee = Estimated value / Rp. 10,000 x Rate x Number of loan days / 10 days - (Original Ijarah x Ijarah Discount Percentage). And what differentiates the size of the discount is the size of the risk that the Islamic pawnshop will accept, if the risk is higher then the discount given will be smaller, and vice versa if the risk that the Islamic pawnshop will accept is higher then the discount given will be bigger.